CV/ SANEAMENTO AMBIENTAL URBANO NA BACIA DO RIO IJUÍ: O ESTADO DA ARTE EM IJUI, RS, 2005-2006 - Pinto, Maria L. C.; Machado, Edinéia G. S.; Bertoldo, Adriana; Lacorth, Rosemeri L. (Salão do Conhecimento, 2013)
Resumo